What you get from what you see: Parametric assessment of visual processing capacity in multiple sclerosis and its relation to cognitive fatigue. (October 2016) - Kluckow, Steffen W.; Rehbein, Jan-Gerrit; Schwab, Matthias; Witte, Otto W.; Bublak, Peter
Abstract: Multiple sclerosis (MS 1 ) is a diffusely disseminated inflammatory disease affecting widespread cerebral networks. Major cognitive impairments are a reduction of processing capacity and mental fatigue, i.e., an "abnormal sense of tiredness or lack of energy". Here, the present study provides the first assessment of the distinct components of visual processing capacity based on a 'theory of visual attention' (TVA 2 ) in MS patients and relates it to measures of subjective as well as (more) objective fatigue. The performance of 36 relapsing-remitting MS patients in a whole report task of brief letter arrays was compared to healthy control subjects matched for gender, age and education. Additionally, the sustained attention test PASAT-3 3 served as a measure of objective fatigue, and the self-report questionnaire MFIS 4 as a measure of subjective fatigue. Results indicate generally diminished processing speed as well as iconic memory buffers, and increased perceptual thresholds in MS patients compared to healthy controls. Block-wise analysis of attentional parameters shows that the processing speed performance of MS patients declines in the second half of the TVA-based test compared to healthy controls and in particular for patients with high versus low objective fatigue. These findings describe which aspects of processing capacity are impaired in MS, and show that fatigue mainly affects speed of processing. Thus, TVA-based assessment provides a novel approach in the determination of cognitive impairments and fatigue in MS. However, further research is required to elucidate the complex relations of processing capacity and cognitive functions in MS.